Literature Review on REITs and Islamic REITs and Lessons Learned for Islamic REITs in Indonesia - Imam Wahyudi Indrawan; Wahyu Ningsih (International Journal of Islamic Economics and Finance (IJIEF), 2019)
Real Estate Investment Trusts (REITs) as a new instrument in many capital markets is an interesting topic. Although not yet to be popular globally, REITs has gained popularity as flexible, cost efficient and profitable real estate investment vehicle for investors as well as provide liquidity for real estate sector, especially in advanced markets like in US, Japan and Singapore. The emergence of Islamic Financial Institutions (IFIs) coincided with increasing popularity of REITs open opportunity for development of Islamic REITs (I-REITs) as competitive but sharia compliant REITs compared to the conventional one. The dominance of Malaysia as market player of I-REITs as well as many underresearched areas open opportunity for betterment of the current I-REITs markets. This paper is a literature review with two objectives. First, to compile and review existing articles on REITs, both conventional and Islamic, and second, to gain lesson learned as material for development of I-REITs in Indonesia as ultimate goal. It is expected that this literature review will generate ideas for future development proposals on I-REITs, particularly in Indonesia. This study found that literature on I-REITs is relatively thin compared to its conventional counterparts, and Indonesia is still left behind in I-REITs development despite regulatory framework is already in force. Therefore, further effort to promote supply and demand of I-REITs in Indonesia should be taken as a way to diversify Islamic investment avenues for sharia oriented investors.